Utilization of Supervisory Technology to Support Risk Concentration Analysis in The Financial Services Authority - Pardiyono; Basuki Hadiprajitno (PT. Maju Malaqbi Makkarana, 2026)
In carrying out its integrated regulatory and supervisory function in the financial services sector, the Financial Services Authority (OJK) receives various reports from Financial Services Institutions (LJK), Issuers, and Public Companies regarding the receipt and distribution of funds. The complexity of funding and financing relationships between financial service actors creates concentration risks that have the potential to disrupt financial system stability. Experiences from the 1998 Indonesian crisis and the 2008 global financial crisis demonstrate that concentration of exposures and interconnectedness between entities can exacerbate systemic risk. This study aims to identify current supervisory data analysis practices and propose the development of a concentration risk analysis that integrates the loan exposures of large debtor groups with their funding sources. The study used a qualitative approach through interviews, observations, and document analysis. The results indicate that OJK supervisors need an integrated concentration risk analysis across various LJKs and customer groups. Currently, the analysis process is still carried out manually, resulting in inconsistent results and difficult to replicate. The implementation of Supervisory Technology (SupTech) can improve supervisory effectiveness while transforming supervisors' tacit knowledge into explicit knowledge that is documented, standardized, and easily shared. This research contributes to the development of technology-based risk monitoring and knowledge management models in the financial services sector.